The Birth of a Legal Institution : The Formation of the Waqf in Third-Century A.H. Ḥanafī Legal Discourse - Hennigan, Peter (Studies in Islamic Law and Society, 2004)
This book present the first sustained analysis of the earliest legal treatises on the Islamic trust, or waqf -- the Aḥkām al-Waqf of Hilāl al-Ra᾿y and the Aḥkām al-Awqāf of al-Khaṣṣāf. The book situates the treastise and their authors within third/ninth century legal culture, and then undertakes a systematic textual analysis of the treatises, examining both the attributes of Ḥanafī legal discourse and how the waqf came to be defined and situated within existing categories of charitable giving, inheritance, bequest and death-sickness. The final chapter focuses on how the waqf was legitimated hermeneutically through traditions of the Prophet and his Companions. The close textual analysis of these treatises is especially important for historians of early Islamic law.